2018
DOI: 10.1016/j.fuel.2018.04.062
|View full text |Cite
|
Sign up to set email alerts
|

Temperature measurement of stored biomass using low-frequency acoustic waves and correlation signal processing techniques

Abstract: As a substitute of traditional fossil fuels, biomass is widely used to generate electricity and heat.The temperature of stored biomass needs to be monitored continuously to prevent the biomass from self-ignition. This paper proposes a non-intrusive method for the temperature measurement of stored biomass based on acoustic sensing techniques. A characteristic factor is introduced to obtain the sound speed in free space from the measured time of flight of acoustic waves in stored biomass. After analysing the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In order to explore the propagation characteristics of sound waves in pulverized coal, Yang et al 119 actually built a pulverized coal acoustic propagation experimental system, carried out research on acoustic attenuation characteristics with different acoustic frequencies, and determined the acoustic frequency band and delay estimation algorithm suitable for detection in pulverized coal. Guo et al 120 built an experimental system for measuring biomass temperature with acoustic method. By introducing characteristic factors, they studied the propagation velocity of sound waves in biomass at different temperatures, and the results showed that there was a good inversion accuracy between sound velocity and coal temperature in the range from 22 °C to 48.9 °C.…”
Section: Research Progress Of Coal Fire Disaster Control Technologymentioning
confidence: 99%
“…In order to explore the propagation characteristics of sound waves in pulverized coal, Yang et al 119 actually built a pulverized coal acoustic propagation experimental system, carried out research on acoustic attenuation characteristics with different acoustic frequencies, and determined the acoustic frequency band and delay estimation algorithm suitable for detection in pulverized coal. Guo et al 120 built an experimental system for measuring biomass temperature with acoustic method. By introducing characteristic factors, they studied the propagation velocity of sound waves in biomass at different temperatures, and the results showed that there was a good inversion accuracy between sound velocity and coal temperature in the range from 22 °C to 48.9 °C.…”
Section: Research Progress Of Coal Fire Disaster Control Technologymentioning
confidence: 99%
“…In order to improve the accuracy of RBF approximation, the RBF approximant is usually extended by polynomial function P k of degree k. Now, equation (5) can be expressed as…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…Acoustic tomography (AT) has been widely used and provided an effective means for temperature distribution visualization owing to the advantages of wide measuring range, noncontacting measurement, and large measurement space. In recent years, the AT method has been widely used in various applications, such as boiler furnaces [1,2], deepsea hydrothermal vents [3,4], stored grain [5,6], and atmospheric surface layer [7,8]. In this paper, we applied the AT method to reconstruct the temperature distribution in a boiler furnace.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the data acquisition accuracy, the sensor output signal should be amplified and meet the input range requirements of the A/D conversion chip. In addition, the amplified signals need to be filtered in order to remove noise interference [7].…”
Section: Signal Conditioning Circuitmentioning
confidence: 99%